Ответ:
Смотри на фото.
Можно, пожалуйста, лучший ответ
Пошаговое объяснение:
5/6(1/3х - 1/5) = 3х + 3. 1/3
5/18х - 5/30 = 3х + 3. 1/3
5/18х - 3х = 3. 1/3 + 5/30
5/18х - 2. 18/18х = 3. 1/3 + 1/6
-2. 13/18х = 3. 2/6 + 1/6
-2. 13/18х = 3. 3/6
-2. 13/18х = 3. 1/2
-49/18х = 7/2
х = 7/2 : (-49/18)
х = 7/2 * (-18/49)
х = 1/1 * (-9/7)
х = -9/7
х = -1. 2/7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Смотри на фото.
Можно, пожалуйста, лучший ответ
Ответ:
Пошаговое объяснение:
5/6(1/3х - 1/5) = 3х + 3. 1/3
5/18х - 5/30 = 3х + 3. 1/3
5/18х - 3х = 3. 1/3 + 5/30
5/18х - 2. 18/18х = 3. 1/3 + 1/6
-2. 13/18х = 3. 2/6 + 1/6
-2. 13/18х = 3. 3/6
-2. 13/18х = 3. 1/2
-49/18х = 7/2
х = 7/2 : (-49/18)
х = 7/2 * (-18/49)
х = 1/1 * (-9/7)
х = -9/7
х = -1. 2/7